Educators in the Perspective of the Hadith of the Prophet Muhammad - Afni Ratna Dewi; Alfiah (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study aims to analyze the definition of educators and how the position, role, and characteristics of educators are from the perspective of hadith, as well as these values when implemented in the context of modern Islamic education. The hadith of the Prophet Muhammad (peace be upon him) provides the basis that educators not only provide knowledge, but also moral examples, spiritual guides, and central figures who determine the achievement of educational goals. The research method used is qualitative with a library research approach through a review of hadith literature and relevant secondary sources. Data were analyzed descriptively and analytically with an emphasis on understanding the meaning of hadith related to the role of educators. The results of the study show that the Prophet Muhammad (peace be upon him) has exemplified the role of ideal educators through compassion, patience, exemplary behavior, and sincerity in teaching. The hadiths that touch on the position of teachers emphasize that educators have a noble position because they are intermediaries of knowledge and shape morals, thus being able to produce a generation of Muslims who are knowledgeable, moral, and responsible.